Molecular detection and identification of Tomato leaf curl New Delhi virus associated with yellow mosaic and leaf curl disease of Luffa cylindrica in India - P.K. SHARMA, S.K. RAJ; G.P. RAO*, A.K. TIWARI, S.K. SNEHI, M.S. KHAN, (Indian Phytopathology, 2012)
Typical yellow mosaic and leaf curling symptoms were observed on Luffa cylindrica during a survey in 2007-08 at Siddharthnagar, Kushinagar and Gorakhpur of eastern Uttar Pradesh, India. The disease incidence was significant (40%) and severity of symptoms was high. The population of whiteflies in the fields indicated possible association of the begomovirus with the disease. Therefore, PCR was performed with a pair of begomovirus specific primers using the total DNA extracted from the symptomatic leaves. The PCR resulted in successful amplification of expected size ( 800 bp) amplicon from all the three collected samples. Two such amplicons were cloned, sequenced and consensus sequence data was submitted in GenBank database (Accession no. EU439261). Based on highest 97% and 100% identities at nucleotide and amino acid levels, respectively, and closest phylogenetic relationships with strains of Tomato leaf curl New Delhi virus (ToLCNDV), L. cylindrica begomovirus was considered as a variant of ToLCNDV.